Hypercubes - An Overview - Varghese, Seema (International Journal of Mathematics And its Applications, 2023)
Mathematicians and computer scientists both find the idea of hypercubes, commonly referred to as n-dimensional cubes or tesseracts, to be incredibly interesting. Hypercubes are a higher dimensional analog of the familiar three-dimensional cube. They provide novel insights into the nature of spatial dimensions and their applications. This article attempts to delve into the world of hypercubes, looking at its characteristics, mathematical representations and practical uses.